Communiting Characteristics of Dried Water Chestnut Kernel - Garg, Sanjeev Kumar; Lohani, Umesh Chandra (Journal of Food Science and Technology Nepal, 2013)
The experiments were conducted to study the grinding characteristics of water chestnut in batch grinding process. Power consumption was measured for grinding time ranged from 120 to 360sec at different speed of mill varied from 800 to 1200rpm for the batch sizes of 100, 150 and 200g. For all the batch sizes, it was observed that as the speed of the mill increased, there was an increase in power consumption and found significantly high for the larger batch size. The relation between power consumption and time of grinding was a straight line with negative slope. For a particular batch size and time of grinding, finer the particles were produced in case of higher mill speed. Taking mill speed and time of grinding constant, less fine particles were produced at higher mass size. Harris model was found best suitable to describe the size distribution in batch grinding process. J. Food Sci. Technol. Nepal, Vol. 6 (88-93), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8267